PERBEDAAN AKTIVITAS ANTIOKSIDAN MINUMAN SEGAR DAN MINUMAN INSTAN DARI JAHE (Zingiber officinale var rubrum), PALA (Myristica fragrans Houtt) DAN SERAI (Cymbopogon nardus L) - Dusun, Citra C.; Assa, Jan R.; Taroreh, Mercy I. R. (Jurnal Teknologi Pertanian (Agricultural Technology Journal, 2020)
AbstractThis study aims to obtain fresh and instant drink formulas from ginger, nutmeg and lemongrass that are accepted by the panelists and have the best antioxidant activity. This study used the RAL method with 6 treatments 3 replications, and fresh drink formulations of FA1: ginger 300mL, nutmeg 100mL, lemongrass 100mL, FA2: ginger 300mL, nutmeg 50mL, lemongrass 150mL, FA3: ginger 300mL, nutmeg 25mL, lemongrass 175 mL and instant drinks FA4: ginger 300mL, nutmeg 100mL, lemongrass 100mL, FA5: ginger 300mL, 50mL of nutmeg, 150mL of lemongrass, FA6: ginger 300mL, nutmeg 25mL, lemongrass 175 mL, then analyzed for total phenol content, antioxidant activity as an antidote to free radicals, then using analysis of variance (ANOVA). The results showed that the highest total phenol content was in the FA3 treatment of 10.81 mgGAE / g, and the lowest was in the FA4 treatment of 0.22 mgGAE / g. The results of the analysis of antioxidant activity as an antidote to DPPH free radicals at a concentration of 100ppm showed that the highest percentage of inhibition was obtained in the FA3 treatment of 52.18% and the lowest was in the FA4 treatment, namely 42.59%. Whereas for the IC50 value, the highest value was found in the FA3 treatment with a concentration of 56.8 ppm, and the lowest was in the FA4 treatment with a concentration of 116.05 ppm. The best treatment based on the sensory test of instant drinks, the most preferred by the panelists was in the FA5 treatment with a value of 4.35, and the lowest was in the FA6 treatment with a value of 4. The results of this study can be concluded that the fresh drinks that have the best total phenols are found in the FA3 treatment, where as for instant drinks that have the best total phenols in the FA5 treatment, and for fresh drinks and instant drinks that have the best antioxidant activity are in the FA3 treatment, for pelyan persistic preferences testing FA5.Keywords: Ginger, Nutmeg, Lemongrass, Total Phenol, Antioxidant.